2019
DOI: 10.1515/mgmc-2019-0016
|View full text |Cite
|
Sign up to set email alerts
|

DFT/QTAIM analysis of favipiravir adsorption on pristine and silicon doped C20 fullerenes

Abstract: Fullerenes have received attentions due to their versatile properties. Molecular structures and electronic properties namely binding energy, band gap, electrophilicity index and molecular topological analysis were studied for undoped and silicon doped C20 fullerenes and favipiravir in order to search for possible application of the systems as drug delivery vehicles. Density functional theory (DFT) and quantum theory of atoms in molecules (QTAIM) were used for the research. Molecular structures having the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…38 Alver et al (2019) investigated the adsorption between favipiravir and non-doped or silicon-doped C20 fullerenes, in order to investigate a possible application of the systems as drug delivery vehicles. 39 These authors noticed that all systems have a large dipole moment, being this an essential criterion for drug interaction. 39 Celik et al (2021) investigated antiviral prodrugs such as favipiravir, remdesivir, galidesivir and ribavirin, and their triphosphate metabolites, for the viral RdRp inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…38 Alver et al (2019) investigated the adsorption between favipiravir and non-doped or silicon-doped C20 fullerenes, in order to investigate a possible application of the systems as drug delivery vehicles. 39 These authors noticed that all systems have a large dipole moment, being this an essential criterion for drug interaction. 39 Celik et al (2021) investigated antiviral prodrugs such as favipiravir, remdesivir, galidesivir and ribavirin, and their triphosphate metabolites, for the viral RdRp inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…These structures and tautomers can occur if the energy required for tautomer formation is provided by other sources, such as intermolecular interactions and binding, and may be important in recognizing such structures before exploring their activity in the biological environment. [10] This study aims to investigate two different structures (A and B) and three tautomers of structure A and two tautomers of structure B and transition states between the tautomers and conformer A and B in different environments as a quantum chemical. Besides, the temperature addiction of the thermodynamic parameters such as heat capacity (Cv), entropy (S), zero-point energy, heat capacity at constant pressure was calculated at B3LYP /6-311G(d,p) level in the gas phase for A3 form.…”
Section: Figurementioning
confidence: 99%
“…[9] investigated the adsorption between favipiravir and undoped or silicon doped C60 fullerenes and to assess their possible usage as drug delivery vehicles and also they studied the possible interaction mechanism of C20 and Si-doped C20 fullerenes with favipiravir molecule. [10] They reported structural analysis of favipiravir performed by exploring tautomers formations. They reported that four tautomers could be possible for favipiravir and their stability could be different regarding the values of total energy and also reported that the results indicated that the structure given in Figure 1 was the most stable structure and the next one is F1 by 5 kcal/mol difference in the stability level.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the above resume and in continuation with our interests to study drugs using theoretical methods (Rhyman et al 2018 ; Alver et al 2019 ; Parlak and Alver 2017 ), we were interested to investigate FPV and HCQ working jointly as a drug. Within this aim, we set objectives, namely: (i) to use DFT and QTAIM to understand the nature of the interactions between the two drugs and (ii) to use SwissADME to have insights in the drug capabilities of the combined drugs.…”
Section: Introductionmentioning
confidence: 99%